Online islamic Narrative - Adeni, Adeni (STAI Bumi Silampari, 2024)
This paper aims to analyze the trends of digital Islamic narratives: whether to strengthen or reject offline Islamic authorities. Methodologically, this qualitative research focuses on Islamic YouTube channels in Indonesia. The results show that religious narratives in the online space have several tendencies based on three types of groups. First, free and progressive Muslim youth groups create provocative religious content to divide and create a new authority system that is entirely different from offline religious authorities. This group tends to oppose religious authorities in the offline space. Second, young religious fanatics tend to present famous figures (celebrities) they admire and try to strengthen the authority of these figures. Third, mainstream religious groups, such as Nahdlatul Ulama (NU) and Muhammadiyah, and splinter religious groups, such as Salafism-Wahabism, Shia, and Ahmadiyah. Their online religious activities seek to strengthen the authority of their respective groups in a contested manner. It can be seen that religious narratives in the online space are not single but varied, which works on the orientation of each group and exacerbates the complexity of religious narratives in the public sphere. This study contributes to the importance of organizing Islamic digital space so that the narratives voiced are narratives that do not divide people but rather bring peace to others as a manifestation of the values of rahmatan lil alamin.